2001
DOI: 10.1002/1097-4644(20010301)80:3<293::aid-jcb10>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interaction of FHL3 with FHL2 and visualization of their interaction by green fluorescent proteins (GFP) two‐fusion fluorescence resonance energy transfer (FRET)

Abstract: LIM domain proteins are found to be important regulators in cell growth, cell fate determination, cell differentiation and remodeling of the cell cytoskeleton. Human Four-and-a-half LIM-only protein 3 (FHL3) is a type of LIM-only protein that contains four tandemly repeated LIM motifs with an N-terminal single zinc finger (half LIM motif). FHL3 expresses predominantly in human skeletal muscle. In this report, FHL3 was shown to be a novel interacting partner of FHL2 using the yeast two-hybrid assay. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Construction of Vectors to Measure FRET in Cells and Transfections-As noted above, GFP and BFP were discovered and developed by a number of groups (19,20) who enabled these fluorescent proteins to be seen and localized in cells (19 -35), and several groups have begun to use FRET to study the interactions of proteins in cells (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). In our studies, the IFN-␥ receptor complex ( Fig.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Construction of Vectors to Measure FRET in Cells and Transfections-As noted above, GFP and BFP were discovered and developed by a number of groups (19,20) who enabled these fluorescent proteins to be seen and localized in cells (19 -35), and several groups have begun to use FRET to study the interactions of proteins in cells (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). In our studies, the IFN-␥ receptor complex ( Fig.…”
Section: Methodsmentioning
confidence: 91%
“…The association of Bcl-2 and Beclin fused to various mutants of GFP was determined by FRET (22). Additional reports in the last few years have begun to determine the association of proteins in cells with the use of GFP and BFP or cyan fluorescent protein and yellow fluorescent protein pairs (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The use of fluorescence lifetime imaging microscopy can eliminate the need for spectral separation and problems in FRET (36) as we found previously by pure spectral methods (13) because fluorescence lifetime measurements permit calculation of distances between donor and acceptor fluorophores totally independent of FRET (11,12).…”
mentioning
confidence: 99%
“…It has been suggested that FHL2 may act as a transducer of apoptotic signals from the extracellular matrix at the focal adhesion plaques to the mitochondria. Interestingly, FHL2-GFP fusion protein was detected in the mitochondria [41]. FHL2 may also be implicated in radiation-induced apoptosis, as irradiation increases expression of p53.…”
Section: Fhl2 and Apoptosismentioning
confidence: 99%
“…5 GST pull down failed to show interaction between FHL2 and type IIa Na/P i cotransporter. cation of FHL2 in a ROCK/Rho GTPases-dependent way [15,27,40,41]. UV treatment of NIH3T3 cells also induced nuclear translocation of ectopic Myc-FHL2, but the mechanism was not investigated [15].…”
Section: Fhl2 Expression Pattern In Human Tissuesmentioning
confidence: 99%
See 1 more Smart Citation